2012
DOI: 10.1302/0301-620x.94b8.28350
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in an uncemented, hydroxyapatite-coated total knee replacement

Abstract: A consecutive series of patients with a hydroxyapatite-coated uncemented total knee replacement (TKR) performed by a single surgeon between 1992 and 1995 was analysed. All patients were invited for clinical review and radiological assessment. Revision for aseptic loosening was the primary outcome. Assessment was based on the Knee Society clinical score (KSS) and an independent radiological analysis. Of 471 TKRs performed in 356 patients, 432 TKRs in 325 patients were followed for a mean of 16.4 years (15 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Over the last 3 decades, long-term follow-up studies reported constant improvement in implant survival [2][3][4][5][6][7][8]. In parallel, several prospective studies highlighted significant clinical and functional improvement on composite scores such as Knee injury and Osteoarthritis Outcome Score (KOOS) [9,10], Knee society score (KSS) [11,12], and Western Ontario and McMaster osteoarthritis index (WOMAC) [13,14], or reported satisfaction rates exceeding 80% [14][15][16], confirming that TKR outcomes are generally good.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 3 decades, long-term follow-up studies reported constant improvement in implant survival [2][3][4][5][6][7][8]. In parallel, several prospective studies highlighted significant clinical and functional improvement on composite scores such as Knee injury and Osteoarthritis Outcome Score (KOOS) [9,10], Knee society score (KSS) [11,12], and Western Ontario and McMaster osteoarthritis index (WOMAC) [13,14], or reported satisfaction rates exceeding 80% [14][15][16], confirming that TKR outcomes are generally good.…”
Section: Introductionmentioning
confidence: 99%
“…All patients were invited for a clinical outcome review which was based on the Knee Society clinical score (KSS) and an independent radiological analysis. Of 471 TKAs performed on 356 patients, 432 TKAs on 325 patients were followed for a mean of 16.4 years (15-18) [ 15 ]. Long et al [ 16 ] also evaluated functional outcome after TKA in young and active patients.…”
Section: Nikolaos Rigopoulos and Theofi Los Karachaliosmentioning
confidence: 99%
“…Briefly, the goals of total joint replacement (TJR) implants are to relieve pain and restore function, with limited impact on the surrounding tissues. Studies focusing on long‐term outcomes of total knee replacement have shown survivorship after 15 years ranging from 81.7 to 98.14% . Similarly, studies for total hip replacement showed survivorship after 15 years ranging above 90% .…”
Section: Introductionmentioning
confidence: 99%